(untitled) (Journal of Universal Science Research, 2024)
The microstructure of the surface is an important characteristic associated with properties such as microhardness, wear resistance, fatigue strength, coefficient of friction, thermal and power loads, aero and gas dynamic resistances, etc. Solving problems of gas dynamics in the absence of data on the real structure of the surface with which gas molecules interact makes it difficult to formulate boundary conditions for calculation the transfer of energy and momentum during the flow of bodies .